Newly developed gas-assisted sonodynamic therapy in cancer treatment - Meng Pan; Danrong Hu; Liping Yuan; Yan Yu; Yicong Li; Zhiyong Qian (Elsevier, 2023)
Sonodynamic therapy (SDT) is an emerging noninvasive treatment modality that utilizes low-frequency and low-intensity ultrasound (US) to trigger sensitizers to kill tumor cells with reactive oxygen species (ROS). Although SDT has attracted much attention for its properties including high tumor specificity and deep tissue penetration, its anticancer efficacy is still far from satisfactory. As a result, new strategies such as gas-assisted therapy have been proposed to further promote the effectiveness of SDT. In this review, the mechanisms of SDT and gas-assisted SDT are first summarized. Then, the applications of gas-assisted SDT for cancer therapy are introduced and categorized by gas types. Next, therapeutic systems for SDT that can realize real-time imaging are further presented. Finally, the challenges and perspectives of gas-assisted SDT for future clinical applications are discussed.